PENEGAKAN DAN PENERAPAN HUKUM ISLAM DI INDONESIA (Sebuah Analisis Pertimbangan Sosiologis dan Historis) - Aris, Aris (Jurusan Syariah dan Ekonomi Islam Institut Agama Islam Negeri (IAIN) Parepare, 2015)
This study related to one aspect of the discussion of Islamic law enforcement and the application of Islamic law in Indonesia. The main problem is the sociological and historical consideration of the enforcement and implementation of Islamic law in Indonesia. Enforcement and implementation of Islamic law has grown and developed in the history of Indonesia. The existence of Islamic law in Indonesia appeared along with the presence of Islam in Indonesia. There are several variations of the idea about the practice of Islamic law in the life of the nation as well as some of the obstacles in the enforcement and implementation of Islamic law in Indonesia.